Global ischemic heart disease burden attributable to kidney dysfunction from 1990 to 2021 and projections to 2050: results from the global burden of disease study 2021 - Xia, Meng; Shi, Yingchao; Zhu, Hongtao; Ji, Yanan (Frontiers in Cardiovascular Medicine, 2025)
BackgroundIschemic heart disease (IHD) is the leading cause of death of non-communicable diseases globally, presenting with particularly prominent metabolic risk associated with kidney dysfunction in the middle-aged and older populations. Accordingly, the present study intended to clarify trends in IHD burden attributable to kidney dysfunction from 1990 to 2021, with projection to 2050, in the middle-aged and older populations.MethodsThis study quantified the burden of IHD attributable to kidney dysfunction in middle-aged and older populations from 1990 to 2021 through deaths, disability-adjusted life years (DALYs), and age-standardized rates (ASRs) based on the estimated annual percentage change (EAPC). Autoregressive integrated moving average (ARIMA) and exponential smoothing (ES) models were adopted to predict the changing trends of IHD burden attributable to kidney dysfunction from 2022 to 2050.ResultsBetween 1990 and 2021, both global deaths (from 0.83 million to 1.40 million) and DALYs (from 16.2 million to 26.1 million) from IHD attributable to kidney dysfunction increased in the studied populations. Despite rising absolute numbers, age-standardized death (ASDR) and DALY rates (ASDAR) declined significantly, with EAPC of −0.54 (95% CI: −0.97 to −0.11) and −0.55 (95% CI: −0.85 to −0.25) respectively, primarily driven by regions with high and high-middle SDI. Sex-specific analyses revealed steeper declines among females (ASDR EAPC: −1.71; ASDAR EAPC: −1.55) than males (ASDR EAPC: −1.18; ASDAR EAPC: −1.09), even with consistently higher rates in males. Age-stratified data showed peak ASRs in the >95 age group in 2021, despite consistent rate reductions across all age cohorts since 1990. Projections suggested continued growth in absolute burden through 2050, accompanied by sustained declines in ASDR and ASDAR, revealing both aging and improved age-adjusted disease management over time.ConclusionThis study suggests a decline in the global age-standardized IHD (ASDR/ASDAR) attributable to kidney dysfunction over three decades, yet accompanied by substantial absolute burden, disproportionately impacting lower SDI regions, males and the elderly. Projection to 2050 highlights a rising burden, necessitating prioritized resource allocation, enhanced health literacy, and evidence-based prevention targeting high-risk populations.